Analysis of Students' Mathematical Representation Ability in Solving Ethnomathematics-Based Story Problems Reviewed from Self-Efficacy - Nisa, Dinda Zahrotun; Komala, Elsa; Monariska, Erma (PRISMA, 2025)
This study aims to determine students' mathematical representation ability in solving ethnomathematics-based story problems, to determine students' self-efficacy in mathematics learning and to determine students' mathematical representation ability in solving ethnomathematics-based story problems in terms of self-efficacy. This study uses a descriptive method with a qualitative approach. The subjects of the study were students at one of the State Junior High Schools in Cianjur, class VIII A with a total of 29 students selected by purposive sampling. The instruments were in the form of mathematical representation ability test questions, self-efficacy questionnaires, and interviews based on mathematical representation indicators. The data analysis technique used on the test results and questionnaires was carried out by adding up the scores then categorizing and describing them in words, while the interview results would be described as supporting the results of the students' answers. The results of the data analysis showed that more students had mathematical representation abilities, namely 25 students. In student self-efficacy, it was known that more students were in the moderate category, namely 22 students. In terms of students' mathematical representation ability, viewed from self-efficacy, there are more in the medium category because the self-efficacy of students in the medium category is the largest, as well as their mathematical representation ability, which is also the largest in the medium category, while in the high category of students' self-efficacy, there are still students who have medium mathematical representation ability and in the low category of students' self-efficacy, students have medium mathematical representation ability.